Mawaddah in the Qur'an Perspective of the Tafsir of the Qur'an Al-Majid An-Nur by Hasbi Ash-Shiddieqy - Annisa Mawaddah; Afrizal Nur (Penerbit Hellow Pustaka, 2025)
This study examines the concept of mawaddah in the Qur'an by focusing on Hasbi Ash-Shiddieqy's interpretation in his monumental work Tafsir al-Qur'an al-Majid An-Nur. The word mawaddah, which is often translated as affection or deep love, not only has an emotional meaning, but also a broad spiritual and social dimension. Using a descriptive qualitative method and a thematic interpretation approach (maudhu'i), this study explores various verses containing the term mawaddah, and analyzes how Hasbi interprets and contextualizes it in the life of pluralistic and dynamic Indonesian society. The results of the study show that Hasbi does not limit the meaning of mawaddah to the realm of husband and wife relations alone, but expands it as an ethical value in building relationships between humans, including in the context of interfaith tolerance and social solidarity. Hasbi's interpretation combines the richness of classical interpretation with the spirit of Islamic renewal, making mawaddah a spiritual energy that forms a civilization based on affection and civility. This study emphasizes the importance of developing thematic interpretations that are responsive to the challenges of the times and rooted in Qur'anic values.